Keragaman Genetik Isolat Cendawan Pyricularia oryzae Menggunakan Primer Pot-2 (Rep-PCR) - Tasliah Tasliah; Reflinur Reflinur; Masdiar Bustamam (Jurnal AgroBiogen, 2008)
Rice blast (Pyriculariaoryzae) is one of the most important diseases of rice. It canbe very destructive in the field, when the environmentalconditions are favourable. Information on genetic diversity ofthis pathogen could assist plant breeders in determiningstrategy for a successful control of the disease. This studywas conducted to analyze genetic diversity in P. oryzaeisolates by a pair of Pot-2 primers using the rep-PCRtechnique. These primers were designed from a transposonelement of the entire blast fungus genomic DNA. DNAsamples were extracted from 212 isolates of P. oryzaecollected from two endemic areas of the disease inIndonesia, i.e., Tamanbogo, Lampung, and Sukabumi, WestJava, as well as from some non-endemic areas in NorthSumatra and West Sumatra). Results of the study indicatedthat the 212 isolates could clustered into 21 haplotypes. Themost dominant haplotypes as indicated by their highestfrequency of haplotypes were haplotype Pot 2-019 (54.46%)followed by haplotype Pot 2-021 (14.73%) and haplotipe Pot2-016 (6.25%). Regardless of origins of the P. oryzae isolates,we found 6 haplotypes from Tamanbogo (out of 117samples), 13 haplotypes from Sukabumi (out of 77 samples),and 11 haplotypes from North Sumatra and West Sumatra(out of 18 isolates). It seems that genetic diversity of the P.oryzae isolates was not affected by the total number ofsamples/isolates, but rather by place of the origin and ricegenotypes from which the isolates were collected.